2021
DOI: 10.1128/msphere.00711-21
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites with SARS-CoV-2 Inhibitory Activity Identified from Human Microbiome Commensals

Abstract: The continued prevalence of COVID-19 and the emergence of new variants has once again put the spotlight on the need for the identification of SARS-CoV-2 antivirals. The human microbiome produces an array of small molecules with bioactivities (e.g., host receptor ligands), but its ability to produce antiviral small molecules is relatively underexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Interestingly, a recent systematic literature review concluded that butyrate inhibits SARS-CoV-2 infectivity by reducing the expression the of ACE2 and TMPRSS2 genes, upregulating the level of ADAM17, a metallopeptidase involved in ACE2 shedding, and upregulating multiple critical antiviral pathways such as TLR (Li J. et al, 2021). Three bacterial metabolites 5-hydroxytryptamine receptor agonist tryptamine, pyrazine 2,5-bis (3-indolylmethyl) pyrazine and N6-(D2isopentenyl) adenosine, exert anti-SARS-CoV-2 activity and share the similar structures and functions to clinical antiviral drugs (Piscotta et al, 2021). High doses of 25-hydroxyvitamin D notably reduced ICU admission for hospitalized patients with COVID-19 (Entrenas Castillo et al, 2020).…”
Section: Relationship Between Microbial Metabolites and Covid-19mentioning
confidence: 99%
“…Interestingly, a recent systematic literature review concluded that butyrate inhibits SARS-CoV-2 infectivity by reducing the expression the of ACE2 and TMPRSS2 genes, upregulating the level of ADAM17, a metallopeptidase involved in ACE2 shedding, and upregulating multiple critical antiviral pathways such as TLR (Li J. et al, 2021). Three bacterial metabolites 5-hydroxytryptamine receptor agonist tryptamine, pyrazine 2,5-bis (3-indolylmethyl) pyrazine and N6-(D2isopentenyl) adenosine, exert anti-SARS-CoV-2 activity and share the similar structures and functions to clinical antiviral drugs (Piscotta et al, 2021). High doses of 25-hydroxyvitamin D notably reduced ICU admission for hospitalized patients with COVID-19 (Entrenas Castillo et al, 2020).…”
Section: Relationship Between Microbial Metabolites and Covid-19mentioning
confidence: 99%
“…Several antiviral agents against SARS-CoV-2 have been developed, however, their efficacy is variable and often dependent upon intervening before the need for intervention is clear. A series of different biomolecules have been proposed as treatments and recently, 3 metabolites produced by components of the human microbiome were shown to be active against SARS-CoV-2 in vitro [22,23].…”
Section: Plos Onementioning
confidence: 99%
“…Given the associations between gut microbiota and cardiometabolic outcomes, developing new therapeutic strategies targeting the gut microbial communities is a promising approach to prevent or treat these diseases. Considerable effort into developing strategies has been used to achieve this goal [ 179 ], including prebiotics [ 180 , 181 ], probiotics [ [182] , [183] , [184] ], fecal microbiota transplantation [ 185 , 186 ], metabolites [ [187] , [188] , [189] , [190] , [191] ], phages [ 192 , 193 ], miRNAs [ 194 ], and hyaluronan [ 195 , 196 ]. In particular, studies in mice have demonstrated that transplantation of cecal microbes from an atherosclerosis-prone strain with high TMA/TMAO levels to a low TMAO-producing and atherosclerosis-resistant strain can enhance production of these pro-atherogenic metabolites with a corresponding increase in aortic lesion formation [ 197 ].…”
Section: Summary and Future Prospectsmentioning
confidence: 99%